STUDENT’S PERCEPTION OF THE POTENTIAL UTILIZATION OF WIND AS A SOURCE OF ENERGY AROUND THE SOUTH COAST OF JAVA - Rahmi, Naura Ahadiyah; Sundarti, Sundarti (EduFisika: Jurnal Pendidikan Fisika, 2021)
Wind is a gas flow that is on a large scale and in large quantities caused by the rotation of the earth and the difference in the air around it. This study aims to analyze students’ knowledge about the potential use of wind as an energy source along the southern coast of Java. This research method was qualitative with respondents from physics education students at the University of Jember batch 2020. The research data collection uses a questionnaire (Google Form). The wind potential around the southern coast of Java has an average speed of 3-8 m/s. In this area, it is very suitable to build a wind power plant because the average wind speed to drive the wind turbine in this power plant is between 5-8 m/s. Students have good knowledge about the potential use of wind as an energy source along the southern coast of Java.